(untitled) (CAHIERS MAGELLANES-NS, 2024)
Gastronomical tourism, a growing facet of cultural tourism, involves traveling to experience the food and culinary practices of a particular region. This paper explores the sociological dimensions of gastronomical tourism in Karnataka, India, focusing on the interplay between local cuisine, culture, and tourism. By analyzing primary data collected from tourists and local stakeholders, this study examines the role of food as a cultural symbol and its influence on tourist behavior and local economies. The paper also discusses the implications of gastronomical tourism for cultural preservation and social change within Karnataka. Key findings suggest that gastronomical tourism not only promotes cultural heritage but also contributes to the socio-economic development of the region. The study concludes with recommendations for leveraging gastronomical tourism to enhance cultural appreciation and sustainable development in Karnataka.